Optimal design of a CsI(Tl) crystal in a SiPM based compact radiation sensor. (November 2015) - Yoo, Hyunjun; Joo, Segyeong; Yang, Shiyoung; Cho, Gyuseong
Abstract: In this study, a compact radiation sensor for integration into mobile applications is proposed consisting of a CsI(Tl) crystal and a silicon photomultiplier with a 3 × 3 mm 2 active area. Considering the size limit of mobile devices, the optimal size of the CsI(Tl) crystal was determined so that it has the best figure of merit (the absolute detection efficiency over the relative energy resolution) in the gamma energy spectrum while satisfying the criteria for the uniformity of the angular response. The final suggested dimensions consist of a cylindrically shaped crystal with a diameter of 5 mm, a total length of 5 mm and a tapered head length of 1 mm. Highlights: The compact radiation sensor consists of a CsI(Tl) crystal and a typical SiPM. The optimal parameters of the crystal are a tapered length and a total length. The parameters are determined by comparing the angular response and the FOM.